Characterisation of Dynamiker SARS-Cov-2 Neutralization Antibody (Nabs) Lateral Flow Immunoassay (LFA) and Enzyme Immunoassays (Eias) Diasorin Liaison RBD and Abbott Igg Quant in Convalescent Sera of SARS-Cov-2 Patients - Bolodeoku, J.; Senessie, A.; Patel, K. (British Journal of Healthcare and Medical Research, 2022)
The EIAs (enzyme immunoassays) that react with the SARS-CoV-2 RBD protein and Spike protein such as DiaSorin S1/S2 IgG and Abbott II IgG correlate very well with neutralizing antibodies. LFAs (lateral flow assays) are the fastest and most convenient tests usually performed within 10 – 15 minutes. Several LFAs have been commercialized to detect IgG, IgM antibodies. In this short report we characterised the Dynamiker SARS-CoV-2 neutralising antibodies (Nabs) LFA with EIAs (DiaSorin Liaisons SARS-CoV-2 RBD antibodies and Abbotts IgG spike antibodies) in the sera of Covid-19 convalescent patients (40 – 93 days) post onset of symptoms. The EIAs (DiaSorin Liaisons SARS-CoV-2 RBD antibodies and Abbotts IgG spike antibodies) were detected in the sera of all the Covid-19 convalescent patients (100%), while the LFA Dynamiker SARS-Cov-2 Nabs were found in the sera of 86% of Covid-19 convalescent patients. In addition, the Dynamiker SARS-CoV-2 Nabs lateral flow immunoassay (LFA) had a positive correlation with the DiaSorin Liaison (RBD) and Abbott IgG Quant (Spike) antibody assays.